Effects of citrate-stabilized gold and silver nanoparticles on some safety parameters of Porphyridium cruentum biomass - Rudi, Ludmila; Cepoi, Liliana; Chiriac, Tatiana; Miscu, Vera; Valuta, Ana; Djur, Svetlana (Frontiers in Bioengineering and Biotechnology, 2023)
Gold and silver nanoparticles are becoming almost ubiquitous due to the accelerated expansion of their emerging applications in many areas. Consequently, their interaction with living organisms is a highly relevant and common concern. The impact of metallic nanoparticles on living cells has been assessed by various researchers as both positive and negative. Depending on the metal, size, and shape of nanoparticles, and the degree of surface functionalization, NPs are used both as stimulators and inhibitors of biological processes. Our research raises the question of how realistic and safe it is to use gold and silver nanoparticles in biotechnologies to grow microalgae, that will later be used to obtain valuable products. This study complements the knowledge on the effects of 10 and 20 nm silver and gold nanoparticles stabilized in citrate on red microalga Porphyridium cruentum. Changes in productivity, lipid content, malondialdehyde (MDA), as well as antioxidant activity of algal biomass have been monitored in dynamics during the life cycle of culture in a closed system. The impact of nanoparticles on the growth curve of microalgae culture was marked by delaying the onset of the exponential growth phase. Excessive accumulation of lipid oxidation products within the first 24 hours of cultivation resulted in altered antioxidant activity of red algae extracts. The addition of Au and Ag nanoparticles during the exponential growth phase of microalga Porphyridium cruentum led to an enhanced lipid accumulation and reduced MDA values in biomass..